Conjugated Polymer–Assisted Grain Boundary Passivation for Efficient Inverted Planar Perovskite Solar Cells - Chen, Wei; Wang, Yingfeng; Pang, Guotao; Koh, Chang Woo; Djurišić, Aleksandra B.; Wu, Yinghui; Tu, Bao; Liu, Fang‐zhou; Chen, Rui; Woo, Han Young; Guo, Xugang; He, Zhubing (Advanced functional materials, 2019)
Grain boundaries in lead halide perovskite films lead to increased recombination losses and decreased device stability under illumination due to defect‐mediated ion migration. The effect of a conjugated polymer additive, poly(bithiophene imide) (PBTI), is investigated in the antisolvent treatment step in the perovskite film deposition by comprehensive characterization of perovskite film properties and the performance of inverted planar perovskite solar cells (PSCs). PBTI is found to be incorporated within grain boundaries, which results in an improvement in perovskite film crystallinity and reduced defects. The successful defect passivation by PBTI yields reduces recombination losses and consequently increases power conversion efficiency (PCE). In addition, it gives rise to improved photoluminescence stability and improved PSC stability under illumination which can be attributed to reduced ion migration. The optimal devices exhibit a PCE of 20.67% compared to 18.89% of control devices without PBTI, while they retain over 70% of the initial efficiency after 600 h under 1 sun illumination compared to 56% for the control devices. A semiconducting conjugated polymer, poly(bithiophene imide), is successfully introduced to perovskite grain boundaries along with augmented grain sizes. This results in effective defect passivation and hence reduced recombination losses and increased efficiency, as well as reduced ion migration and improved stability.